A delayed diagnosis of obturator hernia hoodwinked by previous laparoscopic inguinal hernia repair. Issue 9 (22nd September 2021) - Mercado, Melanie; Diab, Jason; Loi, Ken
Abstract: Obturator hernia is a rare and diagnostically challenging type of pelvic hernia with associated high morbidity and mortality. It is frequently seen in frail, elderly female multiparous patients with non-specific symptoms and signs that may be clouded by multiple gastrointestinal or musculoskeletal comorbidities. This report discusses the case of an 84-year-old woman with refractory groin pain and previous laparoscopic inguinal hernia repair that was misdiagnosed leading to a delayed diagnosis and mortality. Previous laparoscopic repair was a misleading factor that hoodwinked clinicians and surgeons until computed tomography (CT) imaging proved otherwise. In emaciated, elderly female patients presenting with non-specific abdominal or hip pain, early CT imaging can assist in diagnosis when signs or symptoms are unclear. Clinical vigilance and serial examination are important in elderly patients who are often under the care of geriatricians allowing early discovery and treatment of this hernia.